New Oil Crops for Seeds - Lukov Mamadali Kudratvich; Batirov Khidir Fayzievich (Research Parks Publishing LLC, 2022)
Oil radish and winter rape were studied in the field research carried out by the authors between 2012 and 2017 for the purpose of providing seed for new crops for irrigated conditions of the Zarafshan Valley of Uzbekistan. When grown in winter, crops from frost are successfully preserved, but they start to grow from early spring and early summer and can provide a seed yield of oil radish 22.9-26.9 centners / ha and for winter rapeseed 21.1-2. Their biological characteristics allow them to produce 40–60 t/ha of biomass yield at a positive temperature of 600–700 degrees for 40–45 days as well as 3.0–3.5 t/ha of excellent-quality seeds, which is equivalent to a yield of 2.0–2.5 t / ha of edible oil. Additionally, oilseed radish is successfully combined with crops of the cotton–grain complex, and it can be harvested from it three times a year.